KERANGKA ETIS BISNIS ISLAM SEBAGAI SOLUSI KRISIS MORAL EKONOMI MODERN - Aiman Cholil Toatubun; Khairun Nisa'; Hanifah Hanifah; Maimunah Toatubun (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The Development of technology and Globalization triggers a moral crisis, such as corruption, data manipulation, and socio-economic inequality, due to modern economic practices that prioritize profit over human values. This research aims to identify these issues and explore the islamic Business Ethics Framework as an alternative solution. Using a qualitative literature-based approach, data were descriptively analyzed through reduction, display, and conclusion drawing. The findings indicate that implementing honesty, trustworthiness, justice, and transparancy can overcome current moral degradation. This framework strengthens public trust and fosters a humane business system oriented toward collective welfare. The study recommends implementation of corporate social responsibility based on the islamic economy.